2014
DOI: 10.3892/ijmm.2014.1875
|View full text |Cite
|
Sign up to set email alerts
|

FPDHP, a novel anticancer agent, induces cell detachment and caspase-dependent apoptosis in Caki cells

Abstract: Abstract. The inhibition of topoisomerase can suppress the growth of cancer cells and induce apoptosis. The aim of this study was to evaluate the anticancer effects and mechanisms of action of a novel topoisomerase inhibitor, 4-(furan-2-yl)-2-(pyridin-2-yl)-5,6-dihydro-1,10-phenanthroline (FPDHP). FPDHP suppressed the growth of Caki, A549, HT29 and MDA-MB-231 cells, and induced caspase-dependent apoptosis in the Caki cells. In particular, FPDHP also induced caspase-dependent apoptosis and the downregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 24 publications
5
6
0
Order By: Relevance
“…Next, we demonstrated the apoptotic mechanisms of FPDHP in various cancer cells. Like the previous report, 11 FPDHP induces caspase-dependent apoptosis in A549 and Caki cells ( Figure 4A-D). Mitochondria is a very important intracellular organelle, which play a crucial role in apoptosis by releasing AIF and cytochrome c, 16,17 subsequently, the activation of caspase-3 pathway is followed.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Next, we demonstrated the apoptotic mechanisms of FPDHP in various cancer cells. Like the previous report, 11 FPDHP induces caspase-dependent apoptosis in A549 and Caki cells ( Figure 4A-D). Mitochondria is a very important intracellular organelle, which play a crucial role in apoptosis by releasing AIF and cytochrome c, 16,17 subsequently, the activation of caspase-3 pathway is followed.…”
Section: Discussionsupporting
confidence: 85%
“…Previously we demonstrated that FPDHP induces cellular detachment in Caki human renal carcinoma cells. 11 Here, we reconfirmed cell detachment-inducing activity of FPDHP in other cancer cells. Using SRB assay, FPDHP induced cellular detachment of A549, HCT116, and Caki cells in dose (2-20 nM)-and time (1-3 h)-dependent manners, respectively ( Figure 1A-1G).…”
Section: Fpdhp Induced Cellular Detachments In Various Human Cancersupporting
confidence: 58%
See 3 more Smart Citations